ANALISIS PEMASARAN TERASI UDANG DI KELURAHAN BONTANG KUALA KOTA BONTANG - Mawarda; Muhammad Syafril; Elly Purnamasari (Jurnal Pembangunan Perikanan dan Agribisnis, 2021)
This study aimed at knowing the pattern in the marketing channel, marketing margin, marketing efficiency, and the profit earned by the shrimp paste processors in Bontang Kuala Urban Village, Bontang city. The sampling method used here was the census method and Snowball Sampling method with a total sample of 10 people. The result of this study showed that there was a pattern in the marketing channel of shrimp paste in Bontang Kuala Urban Village. The marketing channel consisted of two types, namely, first, a zero-level marketing channel that was from producer to consumer and, second, a level-one marketing channel that was from producer to retailer and then to the consumer. The marketing margin for the processor of shrimp paste business in big round shape was IDR. 4.489/pkg (40 gram), shrimp paste in medium round shape was IDR 5,933/pkg (40 gram), shrimp paste in small round shape was IDR 2,500/pkg (20 gram) and in a cake mold size was IDR 2.500/pkg (20 gram). The efficiency value of marketing by 4 paste of every pack shrimp paste each is in the range of 70%-95%. The business of shrimp paste marketing process is in the efficient category (efficiency value>50%). The profit that was earned was IDR 3,301,805/Month/Respondent. Keyword : Marketing, Profit, Shrimp paste